1996
DOI: 10.1039/cc9960001859
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally friendly catalysis using supported reagents: catalytic epoxidation using a chemically modified silica gel

Abstract: A new heterogeneous catalyst based on a chemically modified mesoporous silica gel possessing immobilised cobalt ions is developed and successfully applied to the epoxidation of alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 2 publications
1
38
0
2
Order By: Relevance
“…Desta forma, as propriedades destas sílicas modificadas quimicamente sofreram alterações, que puderam ser exploradas em várias atividades acadêmicas ou tecnológicas. Assim, a sílica organofuncionalizada encontra principalmente aplicações como fase estacionária para cromatografia [18][19][20][21] ou suporte para materiais com propriedades catalíticas [22][23][24][25][26][27][28][29] . Uma destacada utilização consiste no uso da molécula imobilizada como agente sequestrante para metais, que será enfocado aqui.…”
Section: Figura 1 Esquema Dos Tipos De Grupos Silanóis Normalmente Eunclassified
“…Desta forma, as propriedades destas sílicas modificadas quimicamente sofreram alterações, que puderam ser exploradas em várias atividades acadêmicas ou tecnológicas. Assim, a sílica organofuncionalizada encontra principalmente aplicações como fase estacionária para cromatografia [18][19][20][21] ou suporte para materiais com propriedades catalíticas [22][23][24][25][26][27][28][29] . Uma destacada utilização consiste no uso da molécula imobilizada como agente sequestrante para metais, que será enfocado aqui.…”
Section: Figura 1 Esquema Dos Tipos De Grupos Silanóis Normalmente Eunclassified
“…The resultant modified surfaces can be applied to many areas, such as catalysis and chromatography, and it can serve as a sequestrant agent for cations (15)(16)(17), an ion-exchanger (18), as analytes for electroanalytical purposes (19), and in effluent waste removal from industrial processes (7).…”
Section: Introductionmentioning
confidence: 99%
“…The isotherms are of type IV with a narrow hysteresis loop indicating the existence of mesoporous structure [21]. The position of hysteresis loops shifts slightly to lower relative pressure and the step becomes less steep with the increase of CPTES content in the synthesis gel; this indicates that CA/SBA-15-10 (or ZC/SBA-15-10) has a larger pore size and a narrower distribution than CA/SBA-15-20 (or ZC/SBA- [15][16][17][18][19][20], as shown in Fig. 2b.…”
Section: Catalytic Tests and Analytical Proceduresmentioning
confidence: 99%
“…The grafted vanadium metals showed high activity and leached only slightly from the solid MCM-41-NH 2 -(VO) in benzene hydroxylation. Andrew et al [19] reported a novel heterogeneous catalyst based on a chemically modified mesoporous silica gel with immobilised cobalt ions: cyanide-functionalized mesoporous silica gel was treated with sulfuric acid and then Co 2? ions were introduced into the solid material by ion-exchange.…”
Section: Introductionmentioning
confidence: 99%